Real-time passive cavitation mapping and B-mode fusion imaging via hybrid adaptive beamformer with modified diagnostic ultrasound platform - Zhu, Yifei; Zhang, Guofeng; Zhang, Qi; Luo, Lan; Ding, Bo; Guo, Xiasheng; Zhang, Dong; Tu, Juan (Ultrasonics, 2024)
•Significant advancement in achieving high-quality B-mode/PCM fusion image on modified US system.•A hybrid MV-DMAS adaptive beamforming algorithm developed to enable high-quality PCM.•A high-pass filter selectively detects cavitation signals as lowering tissue scattering impact.•Time-division multiplexing triggering enables B-mode/PCM fusion imaging on modified US system.•Simulations suggest MV-DMAS PCM image quality depends on bubble position and probe pitch width. The implementation of real-time, convenient and high-resolution passive cavitation imaging (PCM) is crucial for ensuring the safety and effectiveness of ultrasound applications related to cavitation effects. However, the current B-mode ultrasound imaging system cannot achieve these functions. By developing a hybrid adaptive beamforming algorithm, the current work presented a real-time PCM and B-mode fusion imaging technique, using a modified diagnostic ultrasound platform enabling time-division multiplexing external triggering function. The proposed hybrid adaptive beamformer combined the advantages of delay-multiply-and-sum (DMAS) and minimum variance (MV) methods to effectively suppress the side lobe and tail-like artifacts, improving the resolution of PCM images. A high-pass filter was applied to selectively detect cavitation-specific signals while removing the interference from the tissue scatters. The system enabled synchronous visualization of tissue structure and cavitation activity under ultrasound exposure. Both numerical and experimental studies demonstrated that, compared with DAS, MV-DAS and DMAS methods, the proposed MV-DMAS algorithm performed better in both axial and lateral resolutions. This work represented a significant advancement in achieving high-quality real-time B-mode and PCM fusion imaging utilizing commercial medical ultrasound system, providing a powerful tool for synchronous monitoring and manipulating cavitation activity, which would enhance the safety and efficacy of cavitation-based applications.